A Novel Canine Mammary Cancer Cell Line: Preliminary Identification and Utilization for Drug Screening Studies - Li, Rifei; Wu, Haoxian; Sun, Yue; Zhu, Jingru; Tang, Jun; Kuang, Yu; Li, Gebin (Frontiers in Veterinary Science, 2021)
Canine malignant mammary tumor is a dangerously fatal neoplastic disease with poor survival in female dogs. The aim of this study was to preliminary characterize a novel canine mammary cancer cell line, B-CMT, from canine primary mammary gland tumor, and to utilize it as a cell model for in vitro screening of possible therapeutic drugs. The successfully established cell line, B-CMT, was cultured over 50 passages. B-CMT has a fast proliferation rate, and a population doubling time (PDT) of 33.6 h. The B-CMT cell line lacked human epidermal growth factor receptor-2 (HER-2), estrogen receptors (ER) and progesterone receptors (PR) expression by qRT-PCR. Compared with MDCK cells, CDH1 expression of CMT cell line was significantly decreased or even absent, but GATA3 expression dramatically increased, while TGF-β expression was at a similar level. Interestingly, the B-CMT cell line from canine primary tumor also showed positive hypoxia inducible factor-1α (HIF-1α) results in immunofluorescence (IF), western blot, and qRT-PCR analysis. Ten days post inoculation with EGFP-B-CMT (B-CMT cells stably expressing EGFP), the experimental mice developed palpable soft tissue masses which histologically resembled the canine primary tumor, and was approved to be derived from B-CMT cell line through detection of EGFP by immunohistochemical (IHC) analysis. Moreover, we investigated the cytotoxicity of five drugs to B-CMT cells, and the results showed that rapamycin and imatinib significantly inhibited the proliferation of the cells in vitro within a certain range of concentration. They also induced cell cycle arrest of B-CMT cells at G1 and G2 phase, respectively. In summary, the results of this report showed that B-CMT cell line might serve as a tool for future studies on tumor microenvironment and drug resistance.